Girl Students' Attitude towards Abortion and Abortion Services in Nepal (Patan Pragya, 2022)
Varieties of social artifacts affect attitudes of adolescent girls towards abortion and abortion services in Nepal. Prevalence of Hindu religious beliefs and traditional socio-cultural norms and values in the existing Nepalese societies, people feel much uncomfortable in the performance of abortion among adolescents. This study explores the attitude of adolescent girl students in our community schools regarding the aforementioned services. The study mainly bases on primary data gained from 250 adolescent girl students of our community schools. It also shows the picture regarding attitude towards abortion and its services of the adolescent's girl students. For such a multi-cultural and religious nation, the traditional values, norms and beliefs have been affecting to perform the services. The result exhibits that almost 61 percent of the respondents trust the existing socio-cultural norms and values that affect the attitude towards abortion and its services, while 57 percent of them believe religious norms and beliefs affect the services. In the same way, only 43 percent of the respondents show confidence in prevailing abortion facilities. This shows that majority of the respondents do not believe on the existing abortion services. A large number of the participants respond that post abortion care is necessary after performing abortion. However, about 74 percent of the respondents believe unnecessary pregnancies should be terminated adopting safety measures rather than letting them to give birth. Resultantly, this study leads us, due to the effects of modernization, globalization and mechanization; adolescent girls in Nepal are in the growing tendency to take abortion performances positively. For this, various activities like awareness campaign, curricula, training and seminar, and media campaign to the marginalized and underprivileged sections work for the decrease of abortion ignorance.